Formalin Levels in Several Types of Salted Fish Before and After Soaking in Rice Washing Water - Angki Purwanti; Husjain Djajaningrat (Jurnal Kesehatan Cendikia Jenius, 2025)
The use of formalin as a preservative in salted fish remains common despite its harmful effects on health. This study aimed to determine the effectiveness of soaking salted fish in rice washing water at ratios of 1:1 and 1:1.5 in reducing formalin levels. The research employed a pretest-posttest design using a laboratory experiment on six types of salted fish selected through purposive sampling from a traditional market in Pondok Gede, Bekasi. The experiment was conducted at the Chemistry Laboratory of the Health Polytechnic of the Ministry of Health Jakarta III from July to December 2024. Four types of salted fish—squid, jambal, pepetek, and sanggeh—were confirmed to contain formalin, with levels ranging from 16 to 29 ppm. The samples were soaked for 20 minutes in rice washing water of two different concentrations and analyzed using colorimetry. The results showed that soaking in 1:1 rice water reduced formalin levels by 26–51%, while soaking in 1:1.5 rice water reduced levels by 55–77%. The higher the concentration of rice washing water, the greater the reduction in formalin. It is concluded that soaking in rice washing water effectively reduces formalin levels without affecting the organoleptic quality. Further research is recommended using other types of salted fish and varied soaking durations.